The significance of a sponsored event on lesser-known brands in a competitive environment. Issue 4 (30th June 2020) - Su, Yiran; Kunkel, Thilo
Abstract : Purpose: Existing research neglected examining the environmental effect of an event on the effectiveness of sponsorship activation in a competitive setting. The purpose of this study is to explore how the event environment impacts consumers' attitudinal and behavioral responses to competitive brands that co-present at an event. Design/methodology/approach: The research comprised an exploratory pre-test and two studies at a sport event with a retailing environment. The exploratory pre-test was used to examine the competitive relationship in the local market between the market leader and the lesser-known sponsoring brand. Study 1 used structural equation modelling to test how the event environment impacts consumers' attitudes toward both brands at the post-consumption stage. Study 2 compared actual sales data of the two competing brands to examine the immediate effect of the sponsorship space on consumption. Findings: The results revealed the event environment had an impact on consumers' brand attitude toward both the lesser known sponsoring brand and the non-sponsoring market leader. However, the effect on the sponsoring brand that activated its sponsorship was influenced by consumer involvement with the event and was more salient. Furthermore, the product sales of the less-known sponsoring brand outperformed that of the market leader that co-presented at the event. Originality/value: This study addresses a call to go beyond exploring the brand image of the sponsoring brands in isolation and holistically examine sponsorship effectiveness. The study contributes to knowledge on both attitudinal and actual behavioural outcomes of sponsorship activation in a competitive environment.